2016
DOI: 10.1021/acs.chemrestox.6b00332
|View full text |Cite
|
Sign up to set email alerts
|

Liabilities Associated with the Formation of “Hard” Electrophiles in Reactive Metabolite Trapping Screens

Abstract: Soft electrophiles (e.g., epoxides, quinones, quinone-imines, quinone-methides, etc.) generated via the oxidative bioactivation of phenyl, phenolic, amino-, and alkylphenolic substituents can be trapped with nucleophiles of comparable softness (e.g., glutathione or cysteine) in reactive metabolite screens. In contrast, hard nucleophiles such as cyanide and amines are frequently utilized to trap hard electrophiles (e.g., iminiums and aldehydes) that result from the oxidative bioactivation of cyclic (or acylic) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 154 publications
1
22
0
Order By: Relevance
“…Following LC‐UV analysis (Figure a) of samples from incubations conducted in the presence or absence of GSH, a major GSH adduct was identified with a mass increase of 190.0023 Da (Figure b), and the resulting MS 2 analysis was triggered by the isotope‐pattern default setting. Further structural analysis suggested that the GlyCys adduct was rearranged to form a thiazolidine adduct with a proposed structure shown in Figure c, comparable with a rearrangement that was previously reported in previous literatures . Overall, this assay successfully identified unusual GSH adducts and provided structure and semiquantitative information of glutathione adducts.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Following LC‐UV analysis (Figure a) of samples from incubations conducted in the presence or absence of GSH, a major GSH adduct was identified with a mass increase of 190.0023 Da (Figure b), and the resulting MS 2 analysis was triggered by the isotope‐pattern default setting. Further structural analysis suggested that the GlyCys adduct was rearranged to form a thiazolidine adduct with a proposed structure shown in Figure c, comparable with a rearrangement that was previously reported in previous literatures . Overall, this assay successfully identified unusual GSH adducts and provided structure and semiquantitative information of glutathione adducts.…”
Section: Resultssupporting
confidence: 83%
“…These settings enable identification of GSH adducts having no glutamyl‐dehydroalanyl‐glycine fragmentation. For example, glutathione conjugates hydrolyzed to other major products, such as cysteinyl‐glycine adducts due to the cleavage of the glutamyl residue; these adducts will not be observed in event 1 ; however, they will be captured and identified after examining spectra of neutral loss (NL) of dehydroalanyl‐glycine (144 Da) as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoiding structural alerts is common practice applied in the rational design of new chemical entities to prevent RM formation . As RM are not easily detected because of their high reactivity, RM screening using trapping agents such as soft and hard nucleophiles (glutathione [GSH], potassium cyanide [KCN], and methoxylamine) in metabolism studies and protein covalent binding in liver microsomal incubations are commonly used . RM‐positive derivatives are then subjected to additional medicinal chemistry modifications to redesign drug candidates with blocked or minimized bioactivation potential.…”
Section: Introductionmentioning
confidence: 99%
“…17,20 As RM are not easily detected because of their high reactivity, RM screening using trapping agents such as soft and hard nucleophiles (glutathione [GSH], potassium cyanide [KCN], and methoxylamine) in metabolism studies and protein covalent binding in liver microsomal incubations are commonly used. 30 RM-positive derivatives are then subjected to additional medicinal chemistry modifications to redesign drug candidates with blocked or minimized bioactivation potential. However, systematically removing "offending" moieties from drug candidates has recently been criticized, since the relationship between structural alerts and adverse effects is not clearcut.…”
mentioning
confidence: 99%